Living on the edge – first survey of loriciferans along the Atacama Trench - Sørensen, Martin V.; Herranz, Maria; Grzelak, Katarzyna; Shimabukuro, Mauricio; Kristensen, Reinhardt M.; Zeppilli, Daniela (European Journal of Taxonomy, 2023)
The fauna of Loricifera along a north-south longitudinal transect following the Atacama Trench was explored. Whereas no loriciferans were collected from the actual trench, the continental slope and surrounding abyssal plains yielded two species of Rugiloricus and two of Pliciloricus. All four species are considered as new to science, but only one of them could be formally described. The new species, Pliciloricus ukupachaensis sp. nov., is closely related with the North Atlantic Pliciloricus leocaudatus, and the two species share different morphological traits, including an enlarged anal field with conspicuous pentagonal and hexagonal fields formed by strong, cuticular ridges. Among other peculiar traits, the new species is characterised by having strongly reduced trichoscalid plates and no double trichoscalids. Comparison with previously published, unidentified specimens suggests that the new species’ distributional range might reach as far as Oregon off the US west coast.